ORTHOGONALITY OF GENERALIZED DERIVATIONS ON SEMIPRIME NONACCESSIBLE RINGS - NAIK*, K. SANKARA; SREENIVASULU, S.; LAKSHMI, P. S. VIJAYA (International Journal of Mathematical Archive, 2018)
This paper gives the properties of orthogonal generalized derivations of semiprime nonaccessible rings. We prove that if (D, d) and (G, g) are generalized derivations of R, then the following conditions are equivalent: ....